Equivalence Analysis of Agricultural Commodity Factors In the Farmer's Exchange Tool Standard in Ramba Village, Wayu, Sidondo II, Sigi Regency - Muhtar Lutfi, Lutfi; Jamaluddin; Hatimah, Husnul (LPPM Universitas Tadulako, 2022)
This study aims to provide an overview of the use of agricultural commodities as a potential alternative medium of exchange for cash equivalents, as well as to study the area and environment in which a commodity can be selected as a medium of exchange. This research method uses a descriptive approach, interviews, focus group discussions, also determines the respondents from productive farmers in the village. The results of the study in 3 (three) target villages showed 1) several commodities; corn, coconut, candlenut, native chicken, can be an alternative medium of exchange other than cash. The effect of this choice is that these commodities have a fairly high level of production and distribution of ownership. 2) Cash reserves for productive farmers are not balanced with the amount of production of some of these commodities which tend to be higher when converted to local cash prices.